Massed practice versus massed practice with stimulation: effects on upper extremity function and cortical plasticity in individuals with incomplete cervical spinal cord injury - Beekhuizen, Kristina S; Field-Fote, Edelle C (Neurorehabilitation and neural repair, 2005)
To determine the effect of massed practice (MP) versus massed practice combined with somatosensory stimulation (MP+SS) on cortical plasticity and function in persons with incomplete tetraplegia. Ten subjects were assigned to either MP or MP+SS. Median nerve stimulation (500 ms train, 10 Hz, 1 ms pulse duration) was delivered at the intensity eliciting a motor threshold response. Training sessions were 5 d/week for 3 weeks at 2 h/session. Outcome measures included 1) motor-evoked potentials (MEPs) elicited via transcranial magnetic stimulation (TMS), motor threshold (MT) and MEP amplitude at 1.2 MT; 2) maximal pinch grip force; 3) Wolf Motor Function Test (WMFT) and Jebsen Hand Function Test. The MP+SS group demonstrated significant improvements (P < 0.05) in pinch grip strength (190%), WMFT scores (52%), and Jebsen test scores (33%), whereas the MP group demonstrated significant improvement (P < 0.05) only in Jebsen test scores (11%). No significant changes were detected in cortical excitability in the MP+SS or MP group. The findings of this preliminary study suggest that MP+SS results in greater increases in pinch strength and timed functional test scores than MP. Optimal stimulation paradigms and training methods are needed to further test this strategy.